Investigating the essential extracellular invadolysin metalloprotease - Feng, Linda (The University of Edinburgh, 2024)
The invadolysin gene was first identified in the Heck laboratory from the study of Drosophila melanogaster mutations that affected chromosome structure and mitotic progression. Invadolysin mutations result in abnormal chromosome condensation and are lethal during the late larval stage. As a novel conserved zinc-metalloprotease, invadolysin is the first protease demonstrated to localise to the surface of lipid droplets in mammalian cultured cells. Mutations of invadolysin influence the development of Drosophila larvae with a decreased triglyceride:protein ratio, which suggests a role for invadolysin in lipid storage and metabolism. In addition, invadolysin has been shown to play an important role in insulin signalling and adipogenesis. As invadolysin is essential for life, it is crucial to explore the biological function of invadolysin in maintaining normal physiology. In silico sequence analysis revealed a potential N-terminal signal sequence in invadolysin, which suggests a secreted form(s) of invadolysin. Recent research published by the Heck laboratory characterized an extracellular form of invadolysin in the soluble fractions of vertebrate blood. Furthermore, analysis of a secreted form of invadolysin in invertebrate haemolymph suggested that invadolysin is sexual dimorphic in adult Drosophila . To optimize the proteomic research technology, I have developed strategies to enrich invadolysin from human blood fractions for further biochemical characterisation of extracellular invadolysin. My results illustrated that the protein expression form of invadolysin differs between human serum and plasma. I have found no evidence suggesting sexually dimorphic forms of invadolysin existing in vertebrates. During early developmental stages of zebrafish (Danio rerio), invadolysin shows dynamic structural changes in yolk and yolk-depleted embryo samples, which suggests a potential role of invadolysin in vertebrate early development. To further explore the potential physiological role(s) of invadolysin, the NAFLD (Non-Alcoholic Fatty Liver Disease) model has been utilized for investigation. Preliminary results showed that the structural forms of invadolysin in plasma are different between non-NAFLD controls and patients with NAFLD. The in vitro hepatic cellular steatosis model and other metabolic associated conditions were used to investigate these differences. The expression form of invadolysin in patients with lung inflammatory diseases, such as idiopathic pulmonary fibrosis (IPF) and coronavirus (COVID-19), have been determined to identify a potential physiological and pathological role of extracellular invadolysin. In the long-term, this project aims to explain whether the extracellular form of invadolysin plays a role in normal physiology and/or serves as a potential biomarker for human diseases.
Keywords: extracellular invadolysin metalloprotease; invadolysin metalloprotease; Drosophila melanogaster mutations; Invadolysin mutations; abnormal chromosome condensation; mammalian cultured cells; lipid droplets in mammalian cultured cells; Mutations of invadolysin; Drosophila larvae; lipid storage; lipid metabolism; insulin signalling; adipogenesis; protein expression form of invadolysin; sexually dimorphic forms of invadolysin; zebrafish (Danio rerio); NAFLD (Non-Alcoholic Fatty Liver Disease) model; idiopathic pulmonary fibrosis (IPF)